Taking emic and etic to the family level: interlinking parents' and children's COVID-19 views and experiences in Germany - Astrid Berner-Rodoreda; Nina Baum; Jonas Wachinger; Kathrin Zangerl; Henriette Hoegl; Till Bärnighausen (BMC, 2024)
Abstract Background COVID-19 impacted families globally, restricting movement, and changing daily routines and family dynamics. In order to explore and contrast children's and parents' experiences and perceptions of life during COVID-19, we used Pike's distinction of emic (an insider's view) and etic (an outsider's view) and adapted the concept to the family level to differentiate between children's and parents' own perspectives (emic) and their view of other family members (etic). Methods Our qualitative study is based on face-to-face in-depth individual interviews with parents (n = 13) and their children (n = 16) and included migrant families as a hitherto underrepresented group in COVID-19 research in Germany. Interviews were recorded, transcribed in NVivo and quality-checked. We employed thematic analysis to explore similarities and differences in perceptions and experiences of children and parents at the family level and across the entire data set. Results We identified the following major themes in parents' and children's experiences: managing role and relationship changes within the nuclear family, coping with social expectations and demands, and re-evaluations of life's priorities. Parents' etic views on children showed strong overlap with children's emic view in terms of physical movement restrictions, experiencing good and tense family times, and internalizing rules. For issues such as experiencing stigma, divorce or language acquisition, parents' views were not reflected in children's accounts. Children's testing experience, by contrast, was more nuanced than parents' perceptions of it. Children's etic views of parents, a perspective rarely found in qualitative research with children, overlapped with mothers' experiences of role strain. Conclusions The consideration of parents' and children's emic and etic perspectives provided deeper insights into family members' experiences, navigation, and views of COVID-19 measures. Applying the emic/etic distinction to the family context enriches the sociology of childhood studies and enables a more nuanced understanding of diverging experiences within families and should thus be further explored within and beyond epidemics in order to guide future pandemic measures.